ChatGPT as an AI Learning Assistant for Enhancing EFL Students’ Writing: A Systematic Literature Riview - Afra Afifah Nurfauzah Alimi; Julita Rafisya; Kurnia Febianti (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The rapid development of Artificial Intelligence (AI), particularly ChatGPT, has significantly influenced English as a Foreign Language (EFL) learning practices. This study aims to examine the role of ChatGPT as an AI-powered learning assistant in enhancing EFL students’ writing skills through a Systematic Literature Review (SLR) approach. The study employed the PRISMA framework to identify, screen, and analyze relevant articles published between 2023 and 2025. The findings reveal that ChatGPT positively contributes to various aspects of writing development, including idea generation, grammatical accuracy, vocabulary enrichment, writing organization, and paragraph coherence. Furthermore, the use of ChatGPT enhances students’ motivation, self-confidence, and autonomy throughout the writing process. However, several challenges were identified, including overreliance on AI technology, academic integrity concerns, and the risk of inaccurate information caused by AI hallucinations. Therefore, ChatGPT should be utilized as a supportive learning tool rather than a substitute for teachers. The study concludes that integrating ChatGPT into EFL writing instruction offers considerable potential for improving learning outcomes when accompanied by the development of AI literacy, digital literacy, and academic ethical awareness.